Hydrogen bonds of a novel resin cement contribute to high adhesion strength to human dentin. Issue 1 (January 2016) - Wu, Wei-Che; Wang, Da-Ming; Lin, Yu-Chen; Dai, Chi-An; Cheng, Kuo-Chung; Hu, Mei-Shan; Lee, Bor-Shiunn
Highlights: A novel resin cement was developed. The phosphate groups of 2MP formed hydrogen bonds with the collagen. The hydrogen bonds prominently decreased in number in the specimens that were stored for 5 months. Abstract: Objective: The detachment of fiber posts from root canals is primarily caused by the loss of adhesion between dentin and cement; therefore, the purpose of this study was to formulate a novel resin cement that improves the bond strength of fiber posts to the dentin–cement interface. Methods: Three concentrations (30, 35, and 40 wt.%) of bis[2-(methacryloyloxy)-ethyl] phosphate (2MP) were prepared as dentin bonding agent components. Isobornyl acrylate (IBOA) and ethylhexylacrylate (EHA) were used as key components to fabricate the resin cement (named IE cement). The adhesive strengths of IE cement to coronal and root canal dentin were tested after placement of specimens in a water bath at 100% humidity and 37 °C for either 24 h or 5 months. The microtensile bond test, the push-out bond test, and the fracture toughness test were performed. Four commercially available resin cements (Nexus ® third generation (NX3), Variolink II, RelyX Unicem, and Panavia F 2.0) were used for comparisons. X-ray photoelectron spectroscopy (XPS) was used to analyze the interaction of collagen extracted from human dentin and 2MP as well as the fracture surfaces of the specimens submitted to the microtensile bond test. Results: The 35% concentration of 2MP, in combination with IBOA and EHA, was the most effective for improving the IE cement's bond strength to dentin. The XPS results revealed that the phosphate groups of 2MP formed hydrogen bonds with the collagen and that such bonds prominently decreased in number in the specimens that were stored for 5 months. Significance: The combination of 2MP, IBOA, and EHA can effectively increase the adhesive strength of IE cement to dentin via hydrogen bond formation.